2021
DOI: 10.3390/math9243176
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Nanofluid Flow and Heat Transfer Past an Inclined Surface

Abstract: This paper examines the hybrid nanoparticles and the magnetic field impacts on the mixed convection boundary layer flow and heat transfer caused by an inclined shrinking–stretching surface in a hybrid nanofluid. Silver (Ag) is added into a MgO–water nanofluid to form Ag-MgO–water hybrid nanofluid. By making use of proper similarity transformations, the governing equations are transformed to ordinary differential equations. The problem is numerically solved with the help of the MATLAB function bvp4c. The influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 52 publications
(67 reference statements)
0
6
0
Order By: Relevance
“…The solinit function of the syntax implies the initial mesh point and informed assumptions. Next, the function handle @OdeBC is coded with boundary conditions (13) and (14). The continuous solution's collocation formula is applied uniformly throughout the interval of integration by the bvp4c solver with fourth-order precision.…”
Section: Numerical Methods and Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…The solinit function of the syntax implies the initial mesh point and informed assumptions. Next, the function handle @OdeBC is coded with boundary conditions (13) and (14). The continuous solution's collocation formula is applied uniformly throughout the interval of integration by the bvp4c solver with fourth-order precision.…”
Section: Numerical Methods and Validationmentioning
confidence: 99%
“…The effect of buoyancy force on the flow of a water/Ag − M gO hybrid nanofluid in an inclined porous stretching/contraction sheet was identified by Anuar et al [13]. In a hybrid nanofluid with an inclined contracting-stretching surface, Alabdulhadi et al [14] investigated the effects of hybrid nanoparticles and a magnetic field on the flow and heat transmission of the mixed convection boundary layer. They noticed that silver (Ag) dissolved in a MgO-water nanofluid is treated as a hybrid Ag-MgO-water nanofluid.…”
mentioning
confidence: 99%
“…Their studies revealed that hybrid nanofluids perform better than nanofluids when the magnetic field is applied to both suspensions of particles in a base fluid. Alabdulhadi et al, [68] studied magnetohydrodynamics mixed convection flow of hybrid silver (Ag) and magnesium oxide (MgO) with water as a base fluid over a shrinking/stretching surface. In a similar study, hybrid Ag-MgO/water nanofluid boundary layer flow across an inclined expandable/contracting plate was studied by Anuar et al, [69] concerning the impacts of buoyancy force and suction effects, while Khan et al, [70] researched mixed convection stagnation point flow of an Ag-MgO/water past a vertical plate in a saturated porous medium with Buoyancy effect.…”
Section: Various Hybrid Nanofluidmentioning
confidence: 99%

Exploration of Recent Developments of Hybrid Nanofluids

Nur Syahidah Nordin,
Abdul Rahman Mohd Kasim,
Masyfu’ah Mokhtar
et al. 2024
ARFMTS
“…It was concluded that heat and boundary layer thickness greatly depend on radiation and variable density parametric effects. Alabdulhadi et al [26] addressed the thermal transportation of a hybrid nanofluid prepared by using silver-magnesium oxide suspended in water past the inclined stretching and shrinking sheet. They determined the dual solution to the problem.…”
Section: Introductionmentioning
confidence: 99%